2010
DOI: 10.1038/nature08855
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hippocampal–prefrontal synchrony in a genetic mouse model of schizophrenia

Abstract: Abnormalities in functional connectivity between brain areas have been postulated as an important pathophysiological mechanism underlying schizophrenia 1,2 . In particular, macroscopic measurements of brain activity in patients suggest that functional connectivity between the frontal and temporal lobes may be altered 3,4 . However, it remains unclear whether such dysconnectivity relates to the aetiology of the illness, and how it is manifested in the activity of neural circuits. Because schizophrenia has a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
634
7
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(697 citation statements)
references
References 30 publications
(43 reference statements)
52
634
7
4
Order By: Relevance
“…Research in rodents has shown increasing evidence that HC-PFC coupling is required for spatial WM performance (Gordon, 2011;Jones and Wilson, 2005;Sigurdsson et al, 2010). Findings in humans, however, draw a different picture: several studies have shown that HC-DLPFC coupling seems to decrease with increasing WM load (Axmacher et al, 2008;Esslinger et al, 2009).…”
Section: Hc-pfc Coupling During Wm-good or Bad?mentioning
confidence: 92%
See 1 more Smart Citation
“…Research in rodents has shown increasing evidence that HC-PFC coupling is required for spatial WM performance (Gordon, 2011;Jones and Wilson, 2005;Sigurdsson et al, 2010). Findings in humans, however, draw a different picture: several studies have shown that HC-DLPFC coupling seems to decrease with increasing WM load (Axmacher et al, 2008;Esslinger et al, 2009).…”
Section: Hc-pfc Coupling During Wm-good or Bad?mentioning
confidence: 92%
“…In the rodent literature, evidence has accumulated that HC-PFC coupling is related to spatial WM performance (Gordon, 2011;Jones and Wilson, 2005;Sigurdsson et al, 2010). Owing to the ceiling effect in our paradigm (with respect to performance in the test phase; Supplementary Materials and Methods), a direct correlation of connectivity and RAM performance was not possible.…”
Section: Functional Connectivity Of a Network Comprising Hc Bilateramentioning
confidence: 99%
“…Sigurdson et al [47] (Figure 1) measured the synchronization between the hippocampus and the prefrontal cortex during working memory (WM) in Df(16)A +/-mice which provide a genetic model for the microdeletion on human chromosome 22 (22q11.2). The 22q11.2 microdeletion is one of the largest known genetic risk factors for schizophrenia [48].…”
Section: Neural Synchrony and Translational Researchmentioning
confidence: 99%
“…For example, theta modulation of gamma activity in the prefrontal cortex is prominent during select cognitive tasks 12 and coherent theta rhythm links hippocampus with the amygdala during processing of emotional information. 13,14 Hippocampal theta activity has also been demonstrated in humans in similar conditions, for example, during spatial memory tasks as well as during REM sleep.…”
mentioning
confidence: 99%